Mechanisms, Pathogenesis, Prognosis and Modern Methods of Treatment of Cardiac Arrhythmias - Vladmirovna, Sarkisova Viktoriya (American Journal of Biomedicine and Pharmacy, 2025)
A healthy heart beats in a regular, coordinated manner because electrical impulses in the heart are generated and propagated by myocytes with unique electrical properties that drive consistent and organized contractions of the myocardium. Disorders associated with rhythm and conduction disorders are caused by abnormal formation and/or conduction of these impulses.